2017
DOI: 10.1002/ange.201701362
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Glycoforms Reveal Carbohydrate‐Dependent Bioactivity of Human Saposin D

Abstract: The main glycoforms of the hydrophobic lysosomal glycoprotein saposin D( SapD) were synthesized by native chemical ligation. An approach for the challenging solid-phase synthesis of the fragments was developed. Three SapD glycoforms were obtained following ag eneral and robust refolding and purification protocol. Acrystal structure of one glycoform confirmed its native structure and disulfide pattern. Functional assays revealed that the lipid-binding properties of three SapD glycoforms are highly affected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…It binds sulfatides in soluble stoichiometric complexes, which are recognized by arylsulfatase A as substrates . On the other hand, saposin C and D are lipid‐binding proteins, which can fuse lipid vesicles at low pH values, by that eventually bringing together newly formed ILVs with already processed, hydrolase loaded and BMP containing ILVs. The four saposins A, B, C, and D are generated in the lysosomal compartment by proteolytic cleavage of their precursor protein, prosaposin .…”
Section: Saps Are Essential Cofactors For Lysosomal Ganglioside Catabmentioning
confidence: 99%
“…It binds sulfatides in soluble stoichiometric complexes, which are recognized by arylsulfatase A as substrates . On the other hand, saposin C and D are lipid‐binding proteins, which can fuse lipid vesicles at low pH values, by that eventually bringing together newly formed ILVs with already processed, hydrolase loaded and BMP containing ILVs. The four saposins A, B, C, and D are generated in the lysosomal compartment by proteolytic cleavage of their precursor protein, prosaposin .…”
Section: Saps Are Essential Cofactors For Lysosomal Ganglioside Catabmentioning
confidence: 99%
“…The lysosomal N ‐glycoprotein saposin D (SapD) was synthesized in two segments that were ligated by NCL followed by successful refolding. Functional assays revealed that the lipid‐binding properties of SapD glycoforms are dependent on both the size and the nature of the glycan moiety . The biosynthesis of glycoproteins starts in the endoplasmic reticulum.…”
Section: Post‐translational Modifications and Artificial Peptides To mentioning
confidence: 99%
“…Functional assays revealed that the lipid-binding properties of SapD glycoforms are dependent on both the size and the natureo ft he glycan moiety. [24] The biosynthesis of glycoproteinss tarts in the endoplasmicr eticulum. To prevent the accumulation of deleterious misfoldedg lycoproteins, non-native glycoproteins are captured and converted into their native structures by chaperones.…”
Section: Protein Synthesis Beyond the Ribosome: Advances In Chemical mentioning
confidence: 99%
“…Because of the heterogeneous nature of this posttranslational modification, the investigation of the precise role of different glycans attached to a glycoprotein of therapeutic interest remains a very difficult task. In the last decades, great advances in protein engineering and, even more, in the chemical synthesis and semisynthesis of glycoproteins are giving access to homogeneous glycoproteins as tools for biological studies, thus enabling important progress in glycobiology. At the same time, the increasing rate of approval of glycoprotein therapeutics has fostered the research in the field, giving further impulse to the discovery of new preparation methods and to the studies on the effects of glycosylation on protein properties and functions, thus generating a virtuous circle.…”
Section: Introductionmentioning
confidence: 99%